Sufficient conditions for order-independency in sequential thinning - Kardos, Péter (Acta Cybernetica, 2011)
The main issue of this paper is to introduce some conditions for template-based sequential thinning that are capable of producing the same skeleton for a given binary image, independent of the visiting order of object points. As an example, we introduce two order-independent thinning algorithms for 2D binary images that satisfy these conditions.